2021
DOI: 10.3389/fpls.2021.663017
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Interaction Enhances the Recovery of Endangered Tree Species in the Fragmented Maulino Forest

Abstract: Beneficial plant-associated microorganisms, such as fungal endophytes, are key partners that normally improve plant survival under different environmental stresses. It has been shown that microorganisms from extreme environments, like those associated with the roots of Antarctica plants, can be good partners to increase the performance of crop plants and to restore endangered native plants. Nothofagus alessandrii and N. glauca, are among the most endangered species of Chile, restricted to a narrow and/or limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Few studies have measured photosynthesis in N. alessandrii . Torres-Díaz et al [ 79 ] evaluated the effect of inoculation with a fungal consortium of root endophytes isolated from the Antarctic host plant Colobanthus quitensis on ecophysiological performance (photosynthesis, water use efficiency, and growth) in N. alessandrii and Nothofagus glauca (Phil.) Krasser.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have measured photosynthesis in N. alessandrii . Torres-Díaz et al [ 79 ] evaluated the effect of inoculation with a fungal consortium of root endophytes isolated from the Antarctic host plant Colobanthus quitensis on ecophysiological performance (photosynthesis, water use efficiency, and growth) in N. alessandrii and Nothofagus glauca (Phil.) Krasser.…”
Section: Discussionmentioning
confidence: 99%
“…However, Penicillium species found in Antarctica may already be present in South America, since this cosmopolitan genus, which forms tiny (typically <6 μm × <4 μm) dry spores, is apparently capable of intercontinental dispersal, with all three operational taxonomic units of the genus recorded in Antarctic soils also being found in soils on other continents (Cox et al, 2019). Nevertheless, in order to avoid inadvertent introductions of pathogens into agricultural soils, we advocate the thorough identification of Antarctic endophytic fungi based on DNA sequence data (Torres‐Díaz et al, 2021) and stringent tests of the effects of these fungi on crop performance. It has also been suggested that the introduction of endophytes from Antarctica to South America could alter native soil communities (Núñez et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the introduction of endophytes from Antarctica to South America could alter native soil communities (Núñez et al, 2015). However, the inoculation of Nothofagus with Antarctic isolates of P. rubens and P. bialowiezense has no apparent effects on the diversity or abundance of native rhizosphere bacteria or fungi (Torres‐Díaz et al, 2021), suggesting that these endophytes pose negligible risks to soil microbiome composition. Further research is needed to confirm whether or not the four other endophytes studied here affect native microbiomes and to determine potential shifts in the efficacy of extremophile endophytes in the less extreme habitats of MTEs, which could potentially lead to their decreased effectiveness over time or even switching to negative impacts on host plants under altered environmental conditions (Giauque et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations